Confetti: A World Literatures and Cultures Journal / Un journal de littératures et cultures du monde - Niemann, Alicia; Allard, Marie-Catherine (Université d'Ottawa | University of Ottawa, 2016)
The Confetti journal is the result of the dedication of the students of the Masters in World Literatures and Cultures, a program unique in Canada: bilingual, interdisciplinary, and dynamic. The issue showcases their research and explorations by bringing together works that encompass critical approaches and methodologies to analyze a variety of cultural expressions from around the world. This volume has two sections that remarkably illustrate the breadth of topics covered in our seminars for the 2015-16 academic year: Transition and Transposition / Power and Desire. Le journal Confetti est le résultat du dévouement des étudiants de la Maîtrise en littératures et cultures du monde, un programme unique au Canada : bilingue, interdisciplinaire et dynamique. Il présente leurs recherches et leurs explorations en rassemblant des travaux qui englobent des approches et des méthodologies critiques pour analyser une variété d'expressions culturelles du monde entier. Ce volume comporte deux sections qui illustrent remarquablement l’étendue des thèmes abordés dans le cadre de nos séminaires de l’année académique 2015-16 : Traduction et transposition / Désir et pouvoir.
Keywords: transition; power; desire; transposition